The effect of anisotropy on residual stress values and modification of Serruys approach to residual stress calculations for coatings such as TiN, ZrN and HfN - SARIOĞLU, CEVAT (ELSEVIER SCIENCE SA, 2006)
The residual stresses in literature on hard coatings (e.g., TiN, CrN, HfN and ZrN) are usually calculated using the mechanical elastic constants often determined by indentation technique by assuming isotropic behavior. The effect of anisotropy of the hard coatings on residual stress values such as TiN, ZrN and HfN has been documented using classical technique and Thin Film techniques (fixed incidence multiplane (FIM) Technique). Due to lack of the single crystal data, the anisotropy of coatings has been taken into account through XECs determined experimentally for ZrN, HfN and TiN films. Recently, single crystal elastic constants of the ZrN, HfN and NbN have been measured. In the light of single crystal elastic constant data, residual stresses reported in the literature were reevaluated according to Reuss, Voigt, Hill (or mixed) and Kroner models using the best fitting approach after modifying Serruys approach. The modified Serruys approach captures the anisotropic behavior of coatings such as ZrN and Zr(Hf)N. The residual stress calculations were improved and the residual stress values were significantly increased as high as 30% compared to the previously published data. The best fitting approach (modified Serruys approach) was compared to the procedure used by Perry using experimentally determined XECs. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: zirconium nitride; residual stress; anisotropy; XRD; coatings; X-RAY-DIFFRACTION; THIN-FILMS; CRYSTALLOGRAPHIC TEXTURE; ARC EVAPORATION; SUBSTRATE; MICROSTRUCTURE; DEPOSITION; CONSTANTS; NITRIDES; PVD